Exploratory Study of Patterns of Post Partum Maternal Sexuality - Dewi Mayangsari; Saadah Mujahidah; Ratih Anggraeni (JURNAL KEBIDANAN, 2022)
The perineal rupture that occurs during labor can affect sexuality in postpartum mothers. About 80% of women experience pain during intercourse, lack of vaginal lubrication, and loss of libido in the first 3 months postpartum. The need for sexuality is often the concern of the mother and family, so it is necessary to carry out discussions during pregnancy based on the culture and beliefs of the family. The purpose of this study was to explore sexuality in postpartum mothers at the Bancak Health Center, Semarang Regency. A qualitative research design with a phenomenological approach was used in this study. Snowball sampling was used in this study with 3 primiparous postpartum women participants 15-42 days with grade 1-2 perineal ruptured. There were 5 triangulations, three husbands, a doctor, and a midwife’s coordinator. In-depth interview instrument was used in this study. Test the data with the general approach of inductive analysis, then the next step becomes deductive. Knowledge about sexuality, namely the relationship between husband and wife after the postpartum period, aims to fulfill the spiritual needs of subsistence and bring the relationship between husband and wife closer. However, mothers are reluctant to have sexual intercourse during the postpartum period for fear of the stitches coming off and pain. Postpartum mothers' readiness about sexuality, the husband's support, and the role of midwives in providing explanations about sexuality after the postpartum period play an important role in overcoming problems of sexuality in postpartum mothers.